Daily polyphenol intake from fresh fruits in Portugal: contribution from berry fruits. (17th July 2013) - Pinto, Paula; Cardoso, Susana; Pimpão, Rui Carlos; Tavares, Lucélia; Ferreira, Ricardo Boavida; Santos, Cláudia Nunes
Abstract: Fresh fruits, particularly berries, are rich in polyphenols. These bioactive compounds are important in the prevention of chronic inflammatory diseases. The present study aimed to assess polyphenol intake from fresh fruit in Portugal and the relative contribution of berries to overall intake, using an online semi quantitative food frequency questionnaire. Consumption of processed berry products was also studied. Mean fresh fruit consumption was 365.6 ± 8.2 g/day. Berries accounted for 9% of total fresh fruit intake, from which 80% were due to strawberries. Total polyphenol intake from fresh fruits was 783.9 ± 31.7 mg of Gallic Acid Equivalents (GAE) per day, from which 14% were from berries. Within berries, strawberries accounted for 11% of total polyphenol intake, with the other consumed berries accounting for 3% of the total polyphenol intake per day. Main reasons reported for relative low consumption of berries were market availability and price. The most consumed processed berry product was yogurt.